PELAKSANAAN PERLINDUNGAN HUKUM TERHADAP PENGHADAP PADA AKTA OTENTIK YANG DI UBAH (RENVOOI) NOTARIS YANG TIDAK DIKETAHUI OLEH PARA PENGHADAP - Elvira Novalita; Maryati Bachtiar; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Notary in practice make authentic act can not be separated from the errors, one of which is Article 48 of law number 30 of 2004 on the post of a notary deed explained that “ the contents may not be altered or added, either in in the form of writing deletion, or insertion overlap removal and replace it with another”. As a result of the parties, feels aggrieved over the incident, and the notary are required to be accountable for his actions.To discuss the above issues the authors use the methodology of sociological research the authors conducted interviews with the ministry of law and human right as well as the region riau existing notary office in the city of pekanbaru. The researchers used data analysis is qualitative descriptive meaning is presented in the form of a describtion to describe clearly hopes to obtain a comprehensive picture of the problems in examined.Implementation of the legal protection of the parties to the authentic deed that changed (renvooi) notary unknown by the parties is a notary may be subject to liability incivil sanctions for doing reimbursement or compensation to the injured party on tort committed by a notary. While the legal consequences authentic act is changed (renvooi) notary uunoticed by the parties is the loss to certificate and be deed under the hand because its manufacture does not comply with the provisions of the law office of notary.In order for the notary and the parties avoid all the risks in the form of sanctions or the concellation of the authentic act in the process of making an authentic deed before a notary, the notary and the parties must possess prudence, more meticulous and have good faith in making authentic deed and to comply with applicable laws and based on the moral and ethical.Keyword : responsibilities, notary, deed authentic